"Dual‐Track" platform governance on content: A comparative study between China and United States. Issue 2 (1st June 2022) - Liu, Jinhe; Yang, Le
Abstract: An Internet platform carrying information content has dual properties of content (information) and technology (medium). We deconstruct the complicated relationships of platform governance on content in China and the United States by building a theoretical framework of dual‐track governance of content and technology. China's mechanism of platform governance on content focuses more on content governance, while the U.S. focuses more on technology governance. China and the U.S. is dominated by the state and the market separately, forming the two mechanisms of "Statism with Content Regulation First" and "Marketism with Technology Governance First",  with four different characteristics. TikTok Path, following the "Separation Principle" of content governance and technology governance, is a feasible approach for the platform company that attempts to go abroad to adapt to different or even conflicting governance contexts. 摘要: 互联网平台内在具有内容（信息）和技术（媒介）的双重属性。我们通过构建内容治理和技术治理的"双轨治理"理论框架，试图解构中国和美国平台内容治理的复杂关系。通过对比可以发现中国的平台内容治理更加侧重内容治理，而美国更加侧重技术治理。中国和美国的平台内通治理分别以国家和市场为主导，形成了"内容监管优先的国家主义"和"技术治理优先的市场主义"两种机制，并呈现出四个重要的不同特征。基于双轨治理理论，遵循内容治理和技术治理相对分离原则所形成的"TikTok路径"为试图适应不同甚至冲突的治理环境的跨国平台企业提供了一种可行做法。